2004
DOI: 10.1124/jpet.104.068825
|View full text |Cite
|
Sign up to set email alerts
|

First Demonstration of a Functional Role for Central Nervous System Betaine/γ-Aminobutyric Acid Transporter (mGAT2) Based on Synergistic Anticonvulsant Action among Inhibitors of mGAT1 and mGAT2

Abstract: In a recent study, EF1502 [N-[4,4-bis(3-methyl-2-thienyl)-3-butenyl]-3-hydroxy-4-(methylamino)-4,5,6,7-tetrahydrobenzo [d]isoxazol-3-ol], which is an N-substituted analog of the GAT1-selective GABA uptake inhibitor exo- 5,6,isoxazol-3-ol), was found to inhibit GABA transport mediated by both GAT1 and GAT2 in human embryonic kidney (HEK) cells expressing the mouse GABA transporters GAT1 to 4 (mGAT1-4). In the present study, EF1502 was found to possess a broad-spectrum anticonvulsant profile in animal models of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 34 publications
6
68
0
Order By: Relevance
“…330 Studies with a novel GABA-transporter inhibitor, EF1502, that potently inhibits GAT-1 and GAT-2 (BGT-1)-but not GAT-3 and GAT-4 -indicate that inhibition of GAT-2 potentiates the anticonvulsant activity of GAT-1. 331,332 GAT-3 can be selectively inhibited with SNAP-5114, which enhances GABA-mediated synaptic inhibition in the neocortex, indicating that GAT-3 plays a role in this brain region. 333 Studies in resected tissue from patients with complex partial seizures and hippocampal sclerosis indicate that the expression of GAT-1 is decreased, but that of GAT-3 may be increased, possibly explaining prolonged IPSCs and increased excitability reported in electrophysiological studies with this tissue.…”
Section: Plasma Membrane Gaba Transportersmentioning
confidence: 99%
“…330 Studies with a novel GABA-transporter inhibitor, EF1502, that potently inhibits GAT-1 and GAT-2 (BGT-1)-but not GAT-3 and GAT-4 -indicate that inhibition of GAT-2 potentiates the anticonvulsant activity of GAT-1. 331,332 GAT-3 can be selectively inhibited with SNAP-5114, which enhances GABA-mediated synaptic inhibition in the neocortex, indicating that GAT-3 plays a role in this brain region. 333 Studies in resected tissue from patients with complex partial seizures and hippocampal sclerosis indicate that the expression of GAT-1 is decreased, but that of GAT-3 may be increased, possibly explaining prolonged IPSCs and increased excitability reported in electrophysiological studies with this tissue.…”
Section: Plasma Membrane Gaba Transportersmentioning
confidence: 99%
“…inhibitor, EF1502, has been used in preclinical studies and showed additional anticonvulsant effects when administered with tiagabine (177,178). While we await clinical development of astrocyte specific GATs inhibitors, examining astrocyte GABAergic transport may provide both insight into potential biomarker validation (astrocyte GABA content) and the efficacy of targeting astrocytic GABA transporters in combatting AD pathology.…”
Section: Relevance To Alzheimer's Diseasementioning
confidence: 99%
“…Proof of concept that GAT inhibitors mediate anticonvulsant activity in rodents has been firmly established (Nielsen et al, 1991;White et al, 1993White et al, , 2002White et al, , 2005Madsen et al, 2009Madsen et al, , 2010. Furthermore, it has been demonstrated that an inhibitor of BGT1 having no affinity for GABA i.e., 4,5,6,7-tetrahydrobenzo[d]isoxazol-3-ol (EF1502) when administered in combination with inhibitors of GAT1 (i.e., tiagabine) and N- [4,5,6,, results in a synergistic anticonvulsant effect in audiogenic seizure (AGS)-susceptible Frings mice (White et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that an inhibitor of BGT1 having no affinity for GABA i.e., 4,5,6,7-tetrahydrobenzo[d]isoxazol-3-ol (EF1502) when administered in combination with inhibitors of GAT1 (i.e., tiagabine) and N- [4,5,6,, results in a synergistic anticonvulsant effect in audiogenic seizure (AGS)-susceptible Frings mice (White et al, 2005). Because EF1502 also inhibits GAT1 , additional experiments examining the combinatorial effect of the two GAT1 selective inhibitors tiagabine and LU-32-176 were performed.…”
Section: Introductionmentioning
confidence: 99%